O movimento arcádico no Brasil setecentista: significado político e cultural da Arcádia ultramarina - Carlos Martins Versiani dos Anjos (2015)
This dissertation focuses on the Ultramarine Arcadia, the literary academy created by Cláudio Manoel da Costa, in Minas Gerais, in the second half of the 18th century, which was affiliated to the 'Roman Arcadia'. The study's goal is to discuss the 'Ultramarine Arcadia' as a symbol of a literary movement, grounded on a rhetoric/poetic dialogue Between Brazilian Arcadians, which surpassed the political and territorial borders between the colony and the metropolis. This way, both in the poets' biographies and works, the author traced elements that would identify them as belonging to the same literary group. Aspects in the topics and rhetoric that would differentiate the Ultramarine Arcadians' poetry from that of the 'Portuguese Arcadians' were also defined. Financed by CAPES Foundation, the researcher had access to different archives and documents that helped him to narrow, if not all, many gaps related to the institutionalization of the Arcadia in Minas Gerais, and to certify the 'Ultramarine Arcadia' consistency as a movement that included the ultramarine poets, in a literary transit between Brazil, Italy and Portugal.